Impact of Environmental, Social and Governance Factors on Company Success in Selected Coal Companies in Shanxi Coking Coal Group: Basis of a Strategic Business Model - Li, Boran (Randwick International of Social Science Journal, 2025)
This research investigated the environmental, social and governance (ESG) practices of selective coal companies in Shanxi, China, including the primary factors that impact company success, particularly contributions to the betterment of environment, the well-being of social communities and governance with respect to sustainability. A self-crafted survey questionnaire was floated to five selected subsidiaries of Shanxi Coking Coal Group, a topnotcher coal producer in the Chinese coal industry. The researcher gathered data on the degree of implementation of ESG management practices. Applying descriptive and inferential statistics enabled the researcher to weigh the ESG factors that impacted on their “company success” and from the results, designed an operational model for the Shanxi coal subsidiaries. The findings of the study showed that addressing environmental issues was not a priority concern among the Shanxi coal subsidiaries even though the government imposed draconian measures. Meanwhile from the multiple regression results, the research yielded significant environmental, social, and governance variables that impact company success, namely, efficient use of water, employee rewards and recognition and generous compensation. In addition, statistical results yielded a Business Strategy Model that can serve as a conceptual framework for coal companies implementing ESG practices for sustainable development. The model can be used for further research.